Por uma América Latina mais justa: análise das concepções dos cristãos de esquerda sobre a AL na Revista Paz e Terra (1966-1969) - Pimentel, Layana Karine (2010)
The 1960 decade is characterized by different socio-cultural transformations. Several questions were made and taboos were questioned at any moment. The Catholic Church itself tried to open up to modernity with the Second Vatican Council. Brazil also passed through these questioning, but the country was under strong civil-military authoritarianism. Among the various sectors that resisted the regime, we highlight the Catholic Church and other brazilian Christian denominations, that, although strongly supported the civil-military coup, constituted themselves in one of the most important pillars of the struggle against the established order, spreading democratic ideas and of social changes. The journal “Paz e Terra” was published from 1966 to 1969. It can be seen as the achievement of an ecumenical project, because it is noticeable in its articles a dialogue between the various Christian and non-Christians on taboo issues such as Marxism, wars, sexuality, religion, among others. Thus, it was an important instrument of objection to the government, because discussed strategic issues raised in that socio-cultural context. The main source of this research is the own object of study, the journal “Paz e Terra”. The study also occurred through the Papal encyclical Pacem in Terris and bibliography about the decade of 1960, especially regarding Christian institutions. The purpose of this essay is to discuss some ideas in “Paz e Terra”, mainly regarding Latin America. We seek, therefore, to expose and discuss, based on several articles, the way both the analysis of Latin American problems and their possible solutions appear in the journal.